Measures of Underlying Inflation in Sri Lanka - Gupta, Souvik (IMF Working Papers; Working Paper ;, 2009)
During the first half of 2008, Sri Lanka witnessed significantly higher inflation than most other emerging Asian countries. Inflation has since declined amid declining world commodity prices and tight monetary policy. Given the sensitivity to global commodity prices, a core inflation measure could be useful for monetary policy. The purpose of this paper is to compare the performance of Sri Lanka's existing official measure of core inflation against alternative measures. Our findings suggest that the existing measure does contain information about the future path of headline information, but may be inadequate as a communication tool for the Central Bank.